Comparative Analyses of Impact of Varying Germination Periods on Malt Quality and Wort Characteristics of Sorghum Bicolor (L) Moench and Sorghum Vulgare Varieties - CI, Owuama; OT, Apanpa; MA, Mbahi; PM, Owuama (Journal of Food Technology Research, 2022)
Three Sorghum bicolor [L] Moench and two Sorghum vulgare varieties were steeped for 20 h at 30 ℃ and germinated for 2 to 6 d. The varieties differed in 1000-grain weight, germination energy, germination capacity, water sensitivity, nitrogen, protein, tannin and moisture contents. Sprouts length increased with germination days and varied with sorghum varieties. Malting loss increased with germination days and differed with cultivars. Cold water extract and hot water extract increased from 2-day to 4-day malts and thereafter decreased. Tannin content varied among cultivars, grains>malts>worts. Diastatic power (DP) and amylase activities increased in both sweet and non-sweet sorghum cultivars from day-2 to day-4 malts and then declined. Sweet sorghum malts revealed higher DP (ca 142.1 ºL) than the non-sweet malts (ca 119.6 ºL). Malts of sweet sorghum varieties had -, β- and γ-amylase activities while non-sweet cultivars indicated only - and β-amylase activities. Sweet sorghum worts had more reducing sugars than non-sweet sorghum varieties. Wort-yields (43.9-68.7%) and reducing sugars differed and increased from day-2 to day-4 malts and then decreased. Worts pH (5.1-6.7) varied with cultivars and the sweet generally had higher pH than non-sweet sorghum cultivars. Generally, the 4-day sweet sorghum malts yielded the best quality malts.